Синтез кестеритних шарів для тонкоплівкових сонячних елементів нової генерації - Сокол, Євген Іванович; Клочко, Наталя Петрівна; Кривошеєв, Сергій Юрійович; Момотенко, Олександра Віталіївна; Любов, Віктор Миколайович; Копач, Володимир Романович; Кіріченко, Михайло Валерійович; Зайцев, Роман Валентинович; Волкова, Неоніла Дмитрівна (НТУ "ХПІ", 2014)
Кестерит Cu₂ZnSnS₄ є прямозонним напівпровідником з оптимальною для перетворення сонячної енергії шириною забороненої зони, який містить доступні хімічні елементи і тому визнаний перспективним для масового виробництва тонкоплівкових сонячних елементів. Визначено найбільш сприятливі послідовності і атомні співвідношення компонентів електрохімічно осаджених прекурсорів, досліджено параметри кристалічної структури кестеритів, синтезованих в процесі сульфурізації прекурсорів.

The results of the kesterite Cu₂ZnSnS₄ layers syntheses by sulfurization of the metal stack precursors have been shown. The phase composition, crystal structure and surface morphology of the electrochemically deposited copper, tin and zinc film stacks as metal precursors were researched. The selection of the optimal sequence of the alternating metal films in the precursors and atomic ratios of the electrodeposited precursor components providing maximum content of Cu₂ZnSnS₄ and the acceptable structural parameters of the kesterite crystalline phase in the layers synthesized during their sulfurization has been made. Quantitative X-ray diffraction was carried out to determine the phase content in the synthesized layers. The optical properties of the synthesized sample containing 85 % kesterite phase were investigated. The directions for the improvement of the proposed technology to create the base layers for advanced effective, cheap and affordable kesterite solar cells of a new generation have been proposed.
Synthesis of kesterite layers for thin film solar cells of a new generation
Keywords: електроосадження; прекурсор; сульфурізація; напівпровідник; electrodeposition; kesterite; solar cell; precursor; sulfurization